Education for people with special needs (Journal of Human Sciences, 2023)
The field of special education at the present time occupied a prominent place as a result of the interest of researchers, educators, psychologists, doctors and others in the field of abnormal children. and we can say that the abnormal children issue has been occupying higher levels in the order of priorities.The field of abnormals or special education is one of the educational fields that faced many challenges until it grew and developed rapidly and occupied a prominent position among the various scientific and educational fields in the countries of the world.Since recently, this field was limited to caring for some individuals with visual, auditory, mental and physical disability, and it did not recognize the caring of and educating individuals who suffer from any other type of disabilities outside of these categories. And he did not recognize the care and education of individuals who suffer from any other type of disabilities outside these categories.In this paper, we will explain the advanced teaching methods for this important category/group in society (people of determination), which is aimed to help teachers and specialists gain a positive attitude towards dealing with students with special needs in schools.